MENINGKATKAN KETERAMPILAN MOTORIK HALUS ANAK USIA DINI MELALUI KEGIATAN MOZAIK SAAT PANDEMI DI TK DHARMA WANITA JATEN KECAMATAN JOGOROGO KABUPATEN NGAWI - Vicky Vidyasary; Wiji Antika; Budi Sasomo (Jurnal Anak Bangsa, 2022)
The focus of the problem in this study is the lack of fine motor development in early childhood and the lack of variety of activities for the development of fine motor skills in children at Dharma Wanita Kindergarten, Jaten. This study aims to improve children's fine motor skills through mosaic activities so that children are able to carry out activities that use fine motor skills well. The research method uses a qualitative descriptive approach, involving one teacher as the research subject. The results showed that the efforts made by educators in improving fine motor skills through mosaic activities include: 1) The teacher chooses a picture pattern for the mosaic activity according to the theme, 2) The teacher makes a design of tools and materials that will be used in the mosaic activity, 3) The teacher provides direction in the process of mosaic activities to children, 4) The teacher provides supervision and observation during the process of mosaic activities, 5) The teacher provides an assessment of the results of the mosaic activities.